SARS-CoV-2 IgG seroprevalence in healthcare workers and other staff at North Bristol NHS Trust: A sociodemographic analysis. Issue 3 (March 2021) - Jones, Christopher R.; Hamilton, Fergus W.; Thompson, Ameeka; Morris, Tim T.; Moran, Ed
Highlights: Nosocomial transmission of SARS-CoV-2 between healthcare workers is evident. Ethnicity is associated with SARS-CoV-2 antibody seroprevalence. Socioeconomic factors influence risk of infection with SARS-CoV-2. SARS-CoV-2 screening strategies must adapt to local healthcare contexts. Collider bias can affect the interpretation of observational cohort data.